Maternal Obesity as a Risk Factor for Preterm Delivery in Dichorionic Twin Pregnancies: Maternal Obesity and Preterm Delivery in Twins - Ali, Mubashra; Javeria, .; Bibi, Maryya Haram (Pakistan Journal of Health Sciences, 2024)
The prevalence of maternal obesity has been steadily rising in recent decades, posing a significant global health concern particularly in the field of obstetrics. Objective: To assess the association between maternal obesity and preterm birth in dichorionic twin pregnancies. Methods: This descriptive study was carried at Department of Obstetrics and Gynecology, Khyber Teaching Hospital, Peshawar during the period 1st January 2020 till 31st December 2021. The study included 122 pregnant women in the age range 18 to 45 years diagnosed as dichorionic twin pregnancy presenting with labor. Gestational age at the time of delivery was calculated to record preterm delivery. Pre-pregnancy BMI was retrieved from medical record taking BMI ≥30.0kg/m2 as cut off for obesity. Data were analyzed using SPSS version 25.0. Results: The mean age was 31.2 years with 49.2% (n=60) fell into the age range of 30-39 years. 52.5% (n=64) of the participants were nulliparous. 42.2% patients (n=52) had a bad previous obstetrics history. Maternal obesity was observed in 49.2% patients (n=60). The spearman r value for preterm delivery and BMI was 0.710. Conclusions: Significant proportion of women with dichorionic twins and preterm delivery were found obese. The risk of preterm delivery in dichorionic twins increases with maternal obesity